2020
DOI: 10.1128/aem.02939-19
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Genetic Basis for Carbapenem Resistance in a Coastal Marine Environment

Abstract: Resistance to the “last-resort” antibiotics, such as carbapenems, has led to very few antibiotics being left to treat infections by multidrug-resistant bacteria. Spread of carbapenem resistance (CR) has been well characterized for the clinical environment. However, there is a lack of information about its environmental distribution. Our study reveals that CR is present in a wide range of Gram-negative bacteria in the coastal seawater environment, including four phyla, eight classes, and 30 genera. These bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 84 publications
(109 reference statements)
1
20
0
2
Order By: Relevance
“…The dissemination of AR in seawater may be influenced by discharges from coastal runoff, aquaculture, polluted rivers, and WWTP effluents, which frequently contain resistant bacteria and resistant genes [72][73][74][75][76][77]. A study described that CRB communities in seawater and storm water samples did not differ significantly at the investigated sites, and the phylogenetic analysis showed that their CR isolates often belonged to the same species [25]. CPE, such as Enterobacter spp.…”
Section: Distribution Of Carbapenem Resistance In Marine Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…The dissemination of AR in seawater may be influenced by discharges from coastal runoff, aquaculture, polluted rivers, and WWTP effluents, which frequently contain resistant bacteria and resistant genes [72][73][74][75][76][77]. A study described that CRB communities in seawater and storm water samples did not differ significantly at the investigated sites, and the phylogenetic analysis showed that their CR isolates often belonged to the same species [25]. CPE, such as Enterobacter spp.…”
Section: Distribution Of Carbapenem Resistance In Marine Systemsmentioning
confidence: 99%
“…Thus, local sources, such as stormwaters and rivers, are an important source of CRB in the seawater and may have a significant effect on the composition of CRB in the marine environment (see Figure 1). Furthermore, CR has also been recently detected in the marine environment [25,73,76,[78][79][80]. For example, CRB belonging to a wide range of bacterial taxa, including four phyla, eight classes, and 30 genera, were found in Australian marine and near-shore environments [25].…”
Section: Distribution Of Carbapenem Resistance In Marine Systemsmentioning
confidence: 99%
See 3 more Smart Citations